2012
DOI: 10.1380/ejssnt.2012.114
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transport Property of Nafion Thin Films on MgO(100) with Anisotropic Molecular Structure

Abstract: To investigate the proton transport properties of the Nafion thin films on MgO(100) substrates, impedance measurements of the 60 and 400 nm thick thin films were carried out. The proton conductivity of two thin films were quite lower values compared to that of the commercial Nafion membrane, and the thickness dependence of the proton conductivity was also observed. To investigate in-plane and out-of-plane molecular vibrations in an identical 400 nm thick film of Nafion on the MgO(100) substrate, an infrared p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…This discussion of main-chain orientation can be supported by the work of another research group [64]. Figure 2(g-j) presents the film thickness dependence of the in-plane proton conductivity on quartz [37], MgO [35,36], sputtered Pt [37], and sputtered Au [36] surfaces. All proton conductivities showed lower values than those of a commercially available Nafion membrane [35,65,66].…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…This discussion of main-chain orientation can be supported by the work of another research group [64]. Figure 2(g-j) presents the film thickness dependence of the in-plane proton conductivity on quartz [37], MgO [35,36], sputtered Pt [37], and sputtered Au [36] surfaces. All proton conductivities showed lower values than those of a commercially available Nafion membrane [35,65,66].…”
Section: Introductionmentioning
confidence: 55%
“…Our group reported the highly oriented structure of Nafion thin films on SiO x [34], MgO [35,36], sputtered Pt [37], and sputtered Au [36] surfaces by infrared p-polarized multiple-angle incidence resolution spectrometry (pMAIRS), which was developed by Hasegawa and co-workers [38][39][40], as presented in Figure 2(a-d). IR pMAIRS offers the molecular orientation for each functional group to various functional materials such as derivatives of polythiophene [41,42], porphyrin [43], pentacene [44], fullerene [45], naphthalene diimide [46], phthalimide [47], azulene [48], metal-oxide nanowire [49], polymer brushes [50], and polyimide [51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirically determined condition on a single example induces confusion that the angle set can commonly be employed for some substrates. Nagao studied 12,13 a functionalized polymer thin film prepared on some substrates using the IR pMAIRS technique with an angle set of six angles from 8 to 38 in 6 steps (38 ¼ 8 þ 6 Â 5), which readily revealed chemically new insights. Since the angle set for calibrating MAIRS was determined on a single sample, however, the optimization does not look over a wide variety of substrates with various refractive indices.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study by the author revealed that the proton conductivity of Nafion thin film (400 nm) is much less than that of a commercial membrane. 3 In the thin film, sulfonic acid groups are highly oriented and mutually isolated from each other, producing poor conductive channel formation. Therefore, the proton-conductivegroup orientation is important to improve proton conductivity.…”
mentioning
confidence: 99%